Myotoxic Mushroom Poisoning in Thailand: Clinical Characteristics and Outcomes - Trakulsrichai, Satariya (Int J Gen Med, 2020)
PURPOSE: To describe the clinical characteristics and outcomes of myotoxic mushroom poisoning in Thailand. PATIENTS AND METHODS: We performed a retrospective cohort study of cases of myotoxic mushroom poisoning from the Ramathibodi Poison Center Toxic Exposure Surveillance System during a 5-year period (2012–2016). RESULTS: Forty-one cases were included. Most (53.7%) were male with the average age of 49 years. In three cases, the mushrooms were identified as Russula species by an experienced mycologist. Common presenting symptoms were gastrointestinal (GI) symptoms and myalgia. The median onset of GI symptoms and symptoms suggesting rhabdomyolysis after consuming mushrooms was 2 hours (0.17–24 hours) and 24–48 hours (2–120 hours), respectively. Eight patients who ate the mushrooms together with other patients with rhabdomyolysis had GI symptoms but did not develop rhabdomyolysis. For patients with rhabdomyolysis, acute kidney injury (AKI) and hyperkalaemia occurred in 51.5% and 33.3% of cases, respectively. Median initial and maximum creatine phosphokinase (CPK) levels in patients with rhabdomyolysis were 31,145 and 47,861 U/L, respectively. Fifteen of 17 patients who were investigated for troponin levels had elevated troponin. Three patients had a low ejection fraction. Most patients (95.1%) were admitted to hospital, with a median stay of 5 days. The mortality rate was 26.8%. Treatments included intravenous fluid, urine alkalinization, haemodialysis and peritoneal dialysis. Among patients with rhabdomyolysis, AKI, hyperkalaemia during hospitalisation, maximum CPK level, maximum creatinine level and initial and maximum potassium levels were the factors found to be significantly different between patients who died and those who survived. CONCLUSION: Myotoxic mushroom poisoning had a high mortality rate. Most patients had early or delayed onset of clinical symptoms after mushroom ingestion. Some patients developed severe cardiovascular effects. Early detection, close monitoring (especially serum potassium, creatinine, CPK and cardiac effect) and good supportive care were the main treatment modalities.